2017
DOI: 10.4103/ua.ua_38_17
|View full text |Cite
|
Sign up to set email alerts
|

Schwannoma of the penis, presenting as a scrotal mass, rare entity with an uncommon presentation

Abstract: Schwannomas are benign nerve sheath tumors that are seen either sporadically or in patients of neurofibromatosis. This tumor is common in head, neck, and extremities. Penis is a rare site for this tumor. To the very best of our knowledge, <34 cases of penile schwannoma have been reported in literature till now, but none had presented as scrotal mass. Here, we report a case of penile schwannoma in a 16-year-old male boy who presented in our outpatient department with a slowly growing scrotal mass. Our patient d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Schwannomas are benign tumors of the Schwann cells which produce the myelin sheath that covers the peripheral nerves, which can be found in patients with neurofibromatosis or without it [1][2] . These tumors are frequent in extremities, face or head.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwannomas are benign tumors of the Schwann cells which produce the myelin sheath that covers the peripheral nerves, which can be found in patients with neurofibromatosis or without it [1][2] . These tumors are frequent in extremities, face or head.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the great innervation of the penis, the presence of these tumors constitutes an atypical manifestation with < 200 cases reported in the literature since its first description in 1968 [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Patients consult for a progressive increase in penile swelling [5,6] or a disorder during intercourse [1] as described in the observation. These tumors occur at any age and mainly between 30 and 60 years [1,[5][6][7][8]. The differential diagnosis must be made with all benign or malignant tumors of the penis including the keloid of the penis.…”
Section: Discussionmentioning
confidence: 99%
“…The patient returned to normal sexual activity after one month, with no observed disturbances. Recurrence and malignant degeneration are rare [1,[5][6][7]. Clinical monitoring of this patient should continue for a minimum of 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Penile plexiform schwannomas are extraordinarily rare with only 2 cases having been identified so far out of the 34 published cases of penile schwannomas. Recently, in 2017, Kumar U et al reported an uncommon presentation of sizeable penile schwannoma mimicking a scrotal mass in a 16-year-old boy [8].…”
Section: Discussionmentioning
confidence: 99%